The Effect of Auditor Competency and Self Efficacy on Audit Judgment at Public Accounting Firm in Bali - I G M Wisnu Cahyadi Putra; I B Anom Yasa; I M Suarta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
Auditors in carrying out activities are influenced by many things, starting from the audit environment and applicable audit regulations. The auditor judgment cannot be replaced because it is an inherent part of the audit process itself, therefore, the audit judgment carried out by the auditor must be carried out properly so as to produce true and accurate information. The phenomenon related to the audit judgment that has occurred causes the public to still question the audit judgment carried out by the auditor who is considered unable to protect external parties using financial statements. The population in this study are all auditors who work in Public Accounting Firms in Bali who are listed in the IAPI 2020 directory. The number of samples in this study found 136 auditors who were selected using the saturated sample or census method. The analytical technique used in this research is a partial least square (PLS) modelling technique through the SmartPLS 3.0 application. The results showed that the auditor competency and self-efficacy had a positive and significant effect on the audit judgment at the Public Accounting Firm in Bali.